2015
DOI: 10.1007/s10126-015-9651-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Retrieval of Living Microorganisms from Cryopreserved Marine Sponges Using a Potential-Controlled Electrode

Abstract: The purpose of this study was to develop a novel electrical retrieval method (ER method) for living sponge-associated microorganisms from marine sponges frozen at −80 °C. A −0.3-V vs. Ag/AgCl constant potential applied for 2 h at 9 °C induced the attachment of the sponge-associated microorganisms to an indium tin oxide/glass (ITO) or a gallium-doped zinc oxide/glass (GZO) working electrode. The electrically attached microorganisms from homogenized Spirastrella insignis tissues had intact cell membranes and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…1A). [31][32][33] A large electrode chamber device [31][32][33] was used for collecting microorganisms from the deep-sea sediment core samples. The microelectrode array 35 was formed by the plane ITO electrode fabricated with SiO 2 and water-repellent coating with fluorine compound (Geomatec Co., Ltd.; the contact angle of water droplets is about 115°).…”
Section: Electrode Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). [31][32][33] A large electrode chamber device [31][32][33] was used for collecting microorganisms from the deep-sea sediment core samples. The microelectrode array 35 was formed by the plane ITO electrode fabricated with SiO 2 and water-repellent coating with fluorine compound (Geomatec Co., Ltd.; the contact angle of water droplets is about 115°).…”
Section: Electrode Preparationmentioning
confidence: 99%
“…3,24,30 In our previous study, we found that numerous actinomycetes including the genus Streptomyces could be electrically retrieved from deep-sea sediments 31 and cryopreserved marine sponges. 32 Living microorganisms suspended in nonnutritive solution such as PBS(¹) and artificial seawater (ASW) were selectively attached to a negative potential-applied optically transparent electrode against gravitational force. 31, 32 Microorganisms suspended in Luria-Bertani medium and glucose solution were not attracted to the electrode.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations